AIP Conference Proceedings 1999
DOI: 10.1063/1.57995
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of deep levels in GaInNAs

Abstract: Abstract. This paper presents and discusses the first Deep-Level transient spectroscopy (DLTS) data obtained from measurements carried out on both Schottky barriers and homojunction devices of GaInNAs. The effect of N and In doping on the electrical properties of the GaNInAs devices, which results in structural defects and interface states, has been investigated. Moreover, the location and densities of deep levels related to the presence of N, In, and N+In are identified and correlated with the device performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
2
5
0
1
Order By: Relevance
“…11 The HT1 and HT4 traps have activation energies of 0.18 and 0.59 eV ͑Table I͒, respectively. Abulfotuh et al 12 reported a nitrogen-related shallow hole trap with an activation energy of 0.22 eV. The HT1 trap has an activation energy close to the reported value, thus similar nitrogen-related defects are postulated to be present in our study.…”
Section: B Majority-carrier "Hole… Dlts Measurementssupporting
confidence: 81%
“…11 The HT1 and HT4 traps have activation energies of 0.18 and 0.59 eV ͑Table I͒, respectively. Abulfotuh et al 12 reported a nitrogen-related shallow hole trap with an activation energy of 0.22 eV. The HT1 trap has an activation energy close to the reported value, thus similar nitrogen-related defects are postulated to be present in our study.…”
Section: B Majority-carrier "Hole… Dlts Measurementssupporting
confidence: 81%
“…H3an and H5ag deep traps have activation energies of 0.23eV and 0.25eV, respectively. These values are close to nitrogen-related hole trap with activation energy of 0.22eV that was reported by Abulfotuh et al [42]. Both samples exhibit shallow traps namely H1an(0.06eV), H2an(0.065eV) and H4ag(0.07eV).…”
Section: Deep Level Transient Spectroscopy Characteristics Of As-grown and Annealed Diodessupporting
confidence: 89%
“…Various trap levels have been discovered in GaInNAs by the deep-level transient spectroscopy ͑DLTS͒ technique. 3,4,10,11 Although the variation in the trap activation energy is dependent on the growth condition, two types of trap levels were identified in GaInNAs; namely a trap located at the midgap level and some shallow traps related to nitrogen incorporation. However, despite the identification of the traps, understanding of the contribution of each defect type to the dark current is still lacking.…”
Section: Introductionmentioning
confidence: 99%